“Intervenciones de enfermería en un adolescente con dengue y sus signos de alarma” - Menendez Flores , Meylin Marlene (2024)
Dengue is a viral disease transmitted by mosquitoes of the genus Aedes aegyptide with the greatest global spread, with an increasing incidence geographically in each country, from urban to rural areas. Transmission of the virus occurs between 8 and 12 days after the bite of the infected mosquito, with the mosquito remaining infectious until it dies (1). Therefore, the aim is to analyze the nursing interventions applied in an adolescent with dengue and warning signs, with the purpose of highlighting the importance of knowledge and attention in the management of this disease. Regarding the methodology, a bibliographic and investigative review obtained updated information on dengue and its complications. The nursing care processes that were used involved the NANDA, NIC and NOC taxonomies to structure the interventions and apply them in a systematic and scientific manner, focusing on the patient's basic requirements and needs. Nursing interventions consisted of taking vital signs and peripheral perfusion. In addition, it was carried out by administering intravenous fluids in a controlled and adjusted manner according to medical prescriptions and fluid balance recording. Also, education was provided to the patient and her caregivers on prevention measures. These actions resulted in a notable improvement in the patient's condition, with a reduction in infection and normalization of platelets. Prevention of recurrence was achieved through continuous monitoring of hygiene and care. Emotional support and instruction was provided to the patient and family, focusing on the importance of adherence to treatment and self-care measures.